Takamatsu: diagnosis, clinical features and peculiarities of different forms of the disease - L. A. Yusupovа; E. I. Yunusovа; Z. Sh. Garaeva; G. I. Mavlyutova (Лечащий Врач, 2021)
The article describes the data on the etiology and pathogenesis of phakomatosis, provides a classification, clinic and features of the course of various forms of the disease. Generalized Recklinghausen neurofibromatosis is considered in details. The article describes such angiomatous phakomatoses as Sturge‒Weber‒Krabbe syndrome, Hippel‒Lindau syndrome, the fifth phakomatosis, variants of differential diagnosis of these diseases and possible methods of treatment.